Risk Profile of Hepatitis E Virus from Pigs or Pork in Canada. Issue 6 (7th October 2016) - Wilhelm, B.; Fazil, A.; Rajić, A.; Houde, A.; McEwen, S. A.
Summary: The role and importance of pigs and pork as sources of zoonotic hepatitis E virus (HEV) has been debated in Canada and abroad for over 20 years. To further investigate this question, we compiled data to populate a risk profile for HEV in pigs or pork in Canada. We organized the risk profile (RP) using the headings prescribed for a foodborne microbial risk assessment and used research synthesis methods and inputs wherever possible in populating the fields of this RP. A scoping review of potential public health risks of HEV, and two Canadian field surveys sampling finisher pigs, and retail pork chops and pork livers, provided inputs to inform this RP. We calculated summary estimates of prevalence using the Comprehensive Meta‐analysis 3 software, employing the method of moments. Overall, we found the incidence of sporadic locally acquired hepatitis E in Canada, compiled from peer‐reviewed literature or from diagnosis at the National Microbiology Laboratory to be low relative to other non‐endemic countries. In contrast, we found the prevalence of detection of HEV RNA in pigs and retail pork livers, to be comparable to that reported in the USA and Europe. We drafted risk categories (high/medium/low) for acquiring clinical hepatitis E from exposure to pigs or pork in Canada and hypothesize that the proportion of the Canadian population at high risk from either exposure is relatively small.